Analisis Kesulitan Membaca (Dyslexia) pada Siswa Sekolah Dasar (Studi Kasus pada Salah Satu Siswa Kelas IV SD Negeri 010 Lubuk Keranji Kec. Bandar Petalangan Kab. Pelalawan) - Rizky, Nadia; Alpusari, Mahmud; Mulyani, Eva Astuti (Darul Yasin Al Sys, 2024)
The aim of this research is to determine the factors that cause reading difficulties (dyslexia) in students in class IV elementary school and the efforts of teachers and parents in overcoming reading difficulties experienced by students in class IV elementary school. This type of research is qualitative research using the case study method. The data sources in this research are students, teachers and parents with the research subject being a fourth grade elementary school student. The results of this research are that there are several factors that cause reading difficulties experienced by students, including interest factors, motivation factors, family environmental factors and family economic factors. The efforts teachers and parents have made to overcome reading difficulties (dyslexia) experienced by students are using learning media, increasing self-confidence and providing motivation, and providing study guidance for students with reading difficulties.